Znaczenie i interpretacja terminu bjA - Napierała, Mateusz (Folia Praehistorica Posnaniensia, 2024)
The aim of the article is to highlight the ambiguity of the word bjA and the difficulties in its interpretation, as well as to indicate the correct way of translating this term and to determine the meaning it had for the Egyptians. It will be possible to present this issue through the analysis of preserved texts, especially religious ones, which highlight the multitude of contexts in which it was used. Equally important for the topic will be the presentation of previous interpretation proposals of the word bjA and an indication of their adequacy in the light of the presented state of research. The key point for this article is the presence of different forms of this term written using different characters. Analysis of the way they are combined allows us to trace changes in the methods of recording bjA that influence its use and its importance. Also important in the interpretation of the term bjA is the analysis of the use of metals, especially copper and iron, in ancient Egypt. The development of their metallurgy is an important issue influencing the development of terminology relating to metallurgy of metals. The analysis of the above points will allow us to draw appropriate conclusions and answer the question: how should we translate the term bjA?